Has the Time Come to Stratify and Score SUDEP Risk to Inform People With Epilepsy of Their Changes in Safety? - Shankar, Rohit; Newman, Craig; Gales, Alistair; McLean, Brendan N.; Hanna, Jane; Ashby, Samantha; Walker, Matthew C.; Sander, Josemir W. (Frontiers in Neurology, 2018)
Recent publication of the AAN SUDEP guidance highlighted the importance to American clinicians of making people with epilepsy aware of SUDEP risk. It is the first guideline to do this in the United States. It follows precedent set out in the UK by NICE in 2004. While a significant achievement, the lack of clarity of how to deliver this guidance in an enduring and person-centred manner, raises concerns on how its long term effectiveness in risk mitigation. Shared decision making with an emphasis on delivering person centred communication to foster self-management strategies is increasingly recognised as the ideal model of patient-clinician communication in chronic diseases such as epilepsy. The tension between delivering evidence based risk information, yet tailoring it to the individual is complex. It needs to incorporate the potential for change not only in seizure factors but other health and social factors. Safety advice needs to be dynamic and situation sensitive as opposed to a ‘one off’ discussion. As a significant minority of people with epilepsy have drug-resistant seizures the importance of keeping the advice contextual at different intervals of the person’s life cannot be overstated as many of them are managed in primary care. We present some exploratory work which identifies the need to improve communication at a primary care level and to review risks regularly. Regular reviews using a structured risk factor checklist as a screening tool could identify sooner people who’s health issues are worsening and justify referrals to specialists.